2014
DOI: 10.1039/c4ob00325j
|View full text |Cite
|
Sign up to set email alerts
|

N- and C-alkylation of seven-membered iminosugars generates potent glucocerebrosidase inhibitors and F508del-CFTR correctors

Abstract: The glycosidase inhibitory properties of synthetic C-alkyl and N-alkyl six-membered iminosugars have been extensively studied leading to therapeutic candidates. The related seven-membered iminocyclitols have been less examined despite the report of promising structures. Using an in house ring enlargement/C-alkylation as well as cross-metathesis methodologies as the key steps, we have undertaken the synthesis and biological evaluation of a library of fourteen 2C- and eight N-alkyl tetrahydroxylated azepanes sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…However, increasing the lipophilicity of azepane scaffold 84 via C-2 or N-alkylation, while tuning the configuration of alkyl and hydroxy substituents at C-2 and C-6 respectively (Fig. 14b), birthed E. coli bGLU inhibitors with markedly increased potency and highly conserved selectivity [182]. SAR analysis revealed that a combination of (6S)eOH unit and N-alkylation with hexyl, nonyl or dodecyl produced stronger inhibitors and their potency increased with increasing chain length.…”
Section: Iminosugarsmentioning
confidence: 99%
“…However, increasing the lipophilicity of azepane scaffold 84 via C-2 or N-alkylation, while tuning the configuration of alkyl and hydroxy substituents at C-2 and C-6 respectively (Fig. 14b), birthed E. coli bGLU inhibitors with markedly increased potency and highly conserved selectivity [182]. SAR analysis revealed that a combination of (6S)eOH unit and N-alkylation with hexyl, nonyl or dodecyl produced stronger inhibitors and their potency increased with increasing chain length.…”
Section: Iminosugarsmentioning
confidence: 99%
“…Other examples of cross metatheses where one of the partners is simple and readily available include: (1) ethylene with 1,4-butadiene polymers (depolymerization) [481], and with trans 1,4-polyisoprene (also using 1-octene as well as ethylene) [482]; (2) [486], with an allylated pyrroloindoline system for norcardioazine A and B total synthesis [487], and with an allylated flavonoid derivative for total synthesis of poinsettifolin A [488]; (4) cis 3-hexene with an allyltetrahydroquinoline system for total synthesis of angustureine (including many examples of RCM to form six-membered ring α,β-unsaturated lactams) [489], and with a homoallylamine derivative for synthesis of tetraponerines [490]; (5) various 1-alkene derivatives and vinylated seven-membered ring aminosugars [491];…”
Section: )mentioning
confidence: 99%
“…Although less popular than piperidines and pyrrolidines, azepane iminosugars exhibit interesting properties as either inhibitors [153] or chaperones [154,155] of carbohydrate-processing enzymes. Accordingly, Désiré and co-workers widened the therapeutic potential of azepanes exploring the capacity of a panel of Nand Calkyl seven membered iminosugars 71-78 (with alkyl chains ranging from 4 to 12 carbon atoms) to rescue the activity of the defective F508del-CFTR [156].…”
Section: N-and C-alkyl Azepane Iminosugars As Cftr Correctorsmentioning
confidence: 99%
“…Hence, elaboration of 80 led to 71 and 72 and the corresponding N-alkylated derivatives 73 and 74, while azepanes 75 and 76 were obtained from 81. Synthesis of C-azepanes 77 and 78 was accomplished by cross metathesis of C-allyl azepanes 82 and 83 in the presence of suitable alkenes (Scheme 10) [156]. When evaluated as CFTR correctors in CF-KM4 cells, azepanes 71 and 72 and the corresponding N-alkylated derivatives 73 and 74 showed no significant activity (Figure 16).…”
Section: N-and C-alkyl Azepane Iminosugars As Cftr Correctorsmentioning
confidence: 99%
See 1 more Smart Citation